Analisis Semiotika Makna Sabar Dan Syukur Dalam Film Gadis Diruang Tunggu - Sulistiani, Umi; Syarifudin, Achmad; Hamandia, Muhammad Randicha (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Film in a narrow sense is the presentation of images via a wide screen, but in a broader sense it can also include those broadcast on TV. The film The Girl in the Waiting Room is the result of the reality of people's lives in general. This research is entitled "Semiotics Analysis of the Meaning of Patience and Gratitude in the film Girl in the Waiting Room". What is motivated by patience is not just learning to let things go, but there are types of patience that not many people know about. This research was conducted to find out how the patient form is implemented by the character Hana in the film The Girl in the Waiting Room. The author uses a descriptive qualitative research method with the film Girl in the Waiting Room as the subject of his research. The object of this research is the meaning of patience and gratitude contained in the pieces of visual images contained in the film The Girl in the Waiting Room. This research was conducted by collecting data through observation and documentation techniques. The theory used by researchers is Roland Barthes Semiotics. Denotation and connotation are two stages of the signification system. Denotation is a sign that explains the signifier and signified in reality which produces an explicit, direct and definite meaning. While the connotation is the level that explains the relationship between the signifier and the signified that is not explicit, indirect and uncertain. Based on the research results, there are many scenes that reflect the meaning of patience and gratitude directly and indirectly. A myth that can be taken by the general public with different levels of understanding, the authors hope that the people who watch it will understand the contents of the film Girls in the Waiting Room.